A design study on metal C-ring seals. (November 2022) - Kim, G.H.; Her, N.I.; Kim, H.T.
Abstract: The seals/gaskets are intended to maintain leak-tightness between the two connecting parts instead of welding or soldering. It is advantageous for a repair or maintenance of a system or equipment. However, there is a risk of losing the sealing effect due to stress relaxation or other unexpected events, especially during long-term operations. This study aims to find a configuration of metal C-rings that maximize elastic energy that affects sealing performance through a shape optimization technique. In addition, contact stress was observed, which is also important for the sealing performance. Unlike O-ring seals, the contact point of the metal C-ring seal varies depending on the compression depth. Thus, the size and position of the contact stress were measured in the various compression depths. Besides, the metal C-ring seals are used in a vacuum as well as in pressure environments. Thus, contact stress was evaluated in such environments. For the optimization study, the genetic algorithm (GA) and B-spline were employed, and the outer boundary of the cross-section of the C-ring was determined to be compatible with the existing standards so that it could replace the typical types. Highlights: An optimization study was carried out on metal C-ring seals, and the contact stresses were observed. The thinnest thickness appears at 74° of the optimal shape. The optimal shape improved the spring-back by 33% and the elastic energy by 27% more. The contact points appeared differently depending on the compression depth. The optimal shape showed 4–5% higher contact stress than the typical one.